Performance Evaluation of Using Evotherm in SBS Modified Binder - Kok, Baha Vural; Yilmaz, Mehmet; Akpolat, Mustafa (Asce-Amer Soc Civil Engineers, 2019)
Recently, various types of additives are being used to enhance the properties of bitumen. Until now, few researchers have handled the utilization of different additives in the same binder. In this study, styrene-butadiene-styrene (SBS) and Evotherm were used both separately and in the same blend. Dynamic shear rheometer (DSR) and bending beam rheometer (BBR) tests were applied to SBS and Evotherm modified binders. SBS and Evotherm were added to pure bitumen in three different ratios. Sixteen different combinations were produced using the two additives, and a pure binder in the same binder was evaluated in the DSR test. Eight different combinations were evaluated in the BBR test. The conclusion reached was that the maximum usage of Evotherm (0.9%) induces a 20% reduction in the rutting parameter of both the 5% and 6% SBS modified binders. The 0.5% Evotherm with 4% and 5% SBS modification does not have an adverse effect on rutting performance. Evotherm modification could prevent the stiffness increment that originates from using the SBS additive, especially at high content. Using 0.7% Evotherm with 4% SBS can acquire the pure binder's low temperature performance. (c) 2019 American Society of Civil Engineers.
Keywords: Styrene-butadiene-styrene; Evotherm; Rutting parameter; Low temperature resistance